(untitled) (Bangladesh Journal of Pharmacology, 2015)
Peptic ulcer disease (PUD) is a main source of morbidity and mortality worldwide. It is characterized by erosions in mucosal linings of stomach and duodenum. Non-steroidal anti-inflammatory drugs (NSAIDs) and Helicobacter pylori are mainly responsible for peptic ulcer disease. Histamine receptor blockers and proton pump inhibitors are most prominent therapies in the treatment of peptic ulcer. However, severe adverse effects of NSAIDs have been reported. Therefore, focus is now diverted towards herbal formulations of medicinal plants for the treatment of ulcer. Plants contain different phytoconstituents which are responsible for increasing defensive mechanisms of body against peptic ulcer. The current review focuses on the commonly used gastroprotective plants as antiulcer agents.